Policy diffusion and social rights in advanced democracies 1960-2000 - Carina Schmitt; Herbert Obinger (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2012)
For many years, comparative welfare state research has been afflicted with a sort of methodological nationalism in the sense that countries were treated as independent units. In line with the recent spatial turn in comparative public policy studies, this paper examines with regard to three welfare state programmes whether, in the postwar period, the provision of social rights in 18 Western democracies was shaped by benefit generosity in other countries. We show that diffusion is present but varies by programme and over time. Rather surprisingly, we find that policy diffusion was particularly relevant during the Golden Age.
Keywords: 300